Decoding energy decomposition analysis Machine-learned Insights on the impact of the density functional on the bonding analysis - Oestereich, Toni (Journal of computational chemistry, 2024)
© 2023 The Authors. Journal of Computational Chemistry published by Wiley Periodicals LLC.